Differential Effects of Exercise Programs on Neuregulin 4, Body Composition and Cardiometabolic Risk Factors in Men With Obesity - Saeidi, Ayoub; Shishvan, Sevda R.; Soltani, Mohammad; Tarazi, Fatemeh; Doyle-Baker, Patricia K.; Shahrbanian, Shahnaz; Mollabashi, Shirin S.; Khosravi, Nikoo; Laher, Ismail; Moriarty, Terence A.; Johnson, Kelly E.; VanDusseldorp, Trisha A.; et al. (Frontiers in Physiology, 2022)
Background: Neuregulin 4 (Nrg4) is an adipokine sensitive to energy expenditure and has a potential role in metabolic homeostasis and obesity. The present study examined the effects of 12 weeks of three different exercise training protocols on neuregulin 4 (Nrg4) levels, cardiometabolic risk factors, and body composition parameters in men with obesity. Methods: Sixty adult men with obesity (mean age: 27.60 ± 8.4 yrs.; mean height: 168.4 ± 2.6 cm; mean weight: 96.7 ± 7.2 kg) were randomly allocated into four groups (n=15/group): High-Intensity Interval Training (HIIT), Circuit Resistance Training (CRT), Moderate Intensity Continuous Training (MICT) or a control group. The HIIT protocol involved six bouts of 3-min high-intensity exercise (90% VO2peak) followed by 3-min low-intensity exercise (50% VO2peak). The CRT group performed three circuits of resistance training, where each circuit included 11 exercises at 20% of one-repetition maximum (1RM) and 70% of VO2peak, and with a work-to-rest ratio of 2:1 (40-sec exercise and 20-sec rest) and 60-sec recovery between circuits. The MICT group performed 36 minutes of exercise at 70% of VO2peak. All measurements were taken 72 hours before and after the first and last training sessions. Results: There were significant differences between the groups in fat-free mass (FFM), (effect size (ES): 0.78), fat mass (ES: 0.86), VO2 peak (ES: 0.59), high-density lipoprotein cholesterol (HDL-C) (ES: 0.83), low-density lipoprotein (LDL-C) (ES: 0.79), total cholesterol (TC) (ES: 0.90), triglyceride (TG) (ES: 0.52) glucose (ES: 0.39), insulin (ES: 0.61), HOM-IR (ES: 0.91) and Nrg4 (ES: 0.98) (p<0.05). There were no significant changes in very-low-density lipoprotein cholesterol (VLDL-C) (ES: 0.13) levels, or body weights (ES:0.51) (p>0.05). Levels of Nrg4 were negatively correlated with LDL-C, TC, TG, VLDL-C, glucose, insulin, HOMA-IR (p<0.05) and positively with HDL-C (p<0.05). Conclusion: Our results suggest that HIIT and CRT protocols have greater effects than MICT protocol on Nrg4 levels, metabolic and cardiovascular risk factors, and body composition variables in men with obesity.